Craniopharyngioma: A lower-middle-income-country epidemiology - Muhammad Usman Khalid; Mashal Murad Shah; Mohammad Hamza Bajwa; Farhan A. Mirza; Altaf Ali Laghari; Muhammad Faraz Raghib; Saad bin Anis; Naveed Zaman Akhunzada; Sameen Siddiqi; Syed Ather Enam (Journal of the Pakistan Medical Association, 2022)
Objective: To quantify the frequency of craniopharyngiomas presenting to tertiary care neurosurgical centres, the demographics and mortality rate, and commonly presenting to neurosurgical practice. Methods: Our study was a retrospective cross-sectional analysis of patients admitted at 32 neurosurgical centres between January 1, 2019, and December 31, 2019, with brain tumour. Kruskal Wallis analysis was used to determine normality; normally distributed variables were reported as means with standard deviation, while median with interquartile range was used for non-normally distributed variables. Results: Of 2750 patients with brain tumours, 114 patients presented with craniopharyngioma. The median age at diagnosis was 18 years, with 42 (42.8%) patients below the age of 15, 40 (40.9%) patients aged 15-39, and 16 (16.3%) patients aged 40 and above. There were 70 (61.4%) males and 44 (38.6%) females in our cohort. Gross total resection was performed in 42(36.8%), 45 (39.5%) underwent subtotal resection, 9 (7.9%) underwent CSF diversion only, and 2 (1.8%) had a biopsy. Most of our patients 94(82.5%) presented to public hospitals, with 20 (17.5%) patients presenting to private hospitals (p=0.002). The overall survival at two years was 86.8% in patients with known outcomes, and only 10% of patients died within 30 days of surgery. Conclusion: Craniopharyngiomas comprised a small portion of all brain tumours in our region. They are more common in males and in patients from the lower socioeconomic class. These patients mainly presented to public sector hospitals, and the three highest volume centres were all public sector institutions. The overall survival rate at two years in our region is lower than in other regions. Keywords: Craniopharyngioma, Brain neoplasm, Retrospective study, Epidemiology, LMIC. Continue...